PENYULUHAN PEMBERANTASAN HAMA TIKUS PADA LAHAN PERTANIAN PADI SAWAH PADA KELOMPOK TANI BERSAMA RT 03 DESA PADANG LUAS KECAMATAN KURAU KABUPATEN TANAH LAUT - Wasdiyanta i22026; Rohansyah (Fakultas Pertanian UVAYA Banjarmasin, 2024)
Implementation of community service is carried out by providing outreach activities to the Joint farmer group RT 03 Padang Luas Village which cultivates lowland rice crops, the service method is by direct participant observation, giving farmers an understanding of the characteristics of rat pests, identifying rat pests and carrying out pest control and prevention measures. rats, there needs to be active participation of farmer groups and the implementation of simultaneous rice planting